Menertib ciri utama pusat membeli-belah menggunakan kesepakatan kabur - Abdul Aziz Jemain ,; Khairul Anuar Mohd Ali , (Penerbit ukm, 2005)
In this article fuzzy logic for analyzing qualitative data is discussed. The discussion focuses on the mathematical models for qualitative data and empirical examples are also elaborated. The problem explored for establishing the fuzzy model is about respondents’ consensus on the importance of properties of a shopping centre. In this study ten important properties were analysed based on the opinion of 150 respondents selected randomly among those who were visiting several shopping centres in the Klang Valley